Hysteroscopic cervical features associated with difficult embryo transfer in unselected patients undergoing in vitro fertilization - Yu-Che Ou; Kuan-Hui Huang; Kuo-Chung Lan (Biomedical Journal, 2022)
Background: The most appropriate diagnostic tests for the assessment of the uterine cavity in patients undergoing standard infertility evaluation in daily practice remain unclear. Routine hysteroscopic uterine cavity evaluation before an in vitro fertilization-embyo transfer (IVF-ET) cycle is not a uniformly accepted procedure. However, cervical findings associated with difficult ET have rarely been reported in previous hysteroscopic studies. The main objective of this study was to examine the relationship between cervical finding under flexible outpatient hysteroscopy (OH) and difficult ET. Methods: A cohort clinical study was conducted with 650 patients undergoing their first in vitro fertilization (IVF)/intracytoplasmic sperm injection (ICSI) from January 2010 to December 2017. Of them, 605 women with available embryos underwent transfer cycles. Outpatient hysteroscopies were scheduled during the follicular phase of the menstrual cycle, 1–3 months before starting IVF/ICSI treatment. Results: Among the 650 women who underwent transvaginal sonography (TVS) and OH, abnormal sonographic findings were observed in 51 women (7.8%) in which submucous myoma, endometrial polyp, and endometrial hyperplasia were the most common. Abnormal hysteroscopic intracavitary findings were observed in 158 cases (24.3%) in which endometrial polyp, submucous myoma, and intrauterine adhesions were the most common. These results showed that TVS was specific (100%) but not sensitive (32.3%) compared with OH. Embryo transfer (ET) was difficult in 25% of women with cervical stenosis (CS) or tortuous cervical canal (TC) and was significantly more difficult in women in the TC group (30.7%) than in the CS group (19.6%). Conclusion: OH can identify cervical charactistics associated with a high incidence of difficult ET.